Mitochondrial GWAS and association of nuclear - mitochondrial epistasis with BMI in T1DM patients - Agnieszka H. Ludwig-Słomczyńska; Michał T. Seweryn; Przemysław Kapusta; Ewelina Pitera; Samuel K. Handelman; Urszula Mantaj; Katarzyna Cyganek; Paweł Gutaj; Łucja Dobrucka; Ewa Wender-Ożegowska; Maciej T. Małecki; Paweł P. Wołkow (BMC, 2020)
Abstract Background BMI is a strong indicator of complications from type I diabetes, especially under intensive treatment. Methods We have genotyped 435 type 1 diabetics using Illumina Infinium Omni Express Exome-8 v1.4 arrays and performed mitoGWAS on BMI. We identified additive interactions between mitochondrial and nuclear variants in genes associated with mitochondrial functioning MitoCarta2.0 and confirmed and refined the results on external cohorts: the Framingham Heart Study (FHS) and GTEx data. Linear mixed model analysis was performed using the GENESIS package in R/Bioconductor. Results We find a borderline significant association between the mitochondrial variant rs28357980, localized to MT-ND2, and BMI (β = − 0.69, p = 0.056). This BMI association was confirmed on 1889 patients from FHS cohort (β = − 0.312, p = 0.047). Next, we searched for additive interactions between mitochondrial and nuclear variants. MT-ND2 variants interacted with variants in the genes SIRT3, ATP5B, CYCS, TFB2M and POLRMT. TFB2M is a mitochondrial transcription factor and together with TFAM creates a transcription promoter complex for the mitochondrial polymerase POLRMT. We have found an interaction between rs3021088 in MT-ND2 and rs6701836 in TFB2M leading to BMI decrease (inter_pval = 0.0241), while interaction of rs3021088 in MT-ND2 and rs41542013 in POLRMT led to BMI increase (inter_pval = 0.0004). The influence of these interactions on BMI was confirmed in external cohorts. Conclusions Here, we have shown that variants in the mitochondrial genome as well as additive interactions between mitochondrial and nuclear SNPs influence BMI in T1DM and general cohorts.